Vysa Redux : Narrative in Epic Mahbhrata. - McGrath, Kevin (Anthem studies in south asian literature, aesthetics and culture, 2019)
Vy?sa is the primary creative poet of the Sanskrit epic Mah?bh?rata and 'Vy?sa Redux' examines the many paradoxical dimensions of his narrative virtuosity in the poem where the poet is both the creator of the work and a character within it. Narrative is, in this view, cognitive rather than empirical in its organization.